Pendampingan Digitalisasi Marketing Desa Kebondalem melalui Aplikasi Google Maps: Upaya Meningkatkan Pengembangan UMKM - Nadhiya Hana Aushafina; Ira Wikartika (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
This service aims to increase the marketing and reach of Micro, Small and Medium Enterprises (MSMEs), especially in Kebondalem Village, using digital technology, especially the Google Maps platform. MSMEs have an important role in maintaining economic stability and their ability to survive amidst the Corona outbreak in early 2020 is clear proof. During this time, trade and marketing transformed significantly into digital with the use of various technologies. However, MSMEs in Kebondalem Village face challenges in adopting digital marketing. Therefore, using Google Maps is a relevant solution. Google Maps is a platform that allows MSMEs to show their location visually on a map. The app is designed with a simple interface and is easy to use, even by individuals who are not tech savvy. With Google Maps, it is hoped that MSMEs in Kebondalem Village can expand their market coverage. It will be easier for the public to find and contact MSMEs that are registered on Google Maps, providing opportunities for MSMEs to increase sales and survive in this digital era. Thus, it is hoped that this service can make a positive contribution to the development of MSMEs at the local level and the economy